The association of Wnt-signalling and EMT markers with clinical characteristics in women with endometrial cancer - Ledinek, Živa; Sobočan, Monika; Sisinger, Damjan; Hojnik, Marko; Büdefeld, Tomaž; Potočnik, Uroš; Knez, Jure (Frontiers in Oncology, 2023)
Endometrial cancer is the most common gynecologic malignancy in the developed world. Risk stratification and treatment approaches are changing due to better understanding of tumor biology. Upregulated Wnt signaling plays an important role in cancer initiation and progression with promising potential for development of specific Wnt inhibitor therapy. One of the ways in which Wnt signaling contributes to progression of cancer, is by activating epithelial-to-mesenchymal transition (EMT) in tumor cells, causing the expression of mesenchymal markers, and enabling tumor cells to dissociate and migrate. This study analyzed the expression of Wnt signaling and EMT markers in endometrial cancer. Wnt signaling and EMT markers were significantly correlated with hormone receptors status in EC, but not with other clinico-pathological characteristics. Expression of Wnt antagonist, Dkk1 was significantly different between the ESGO-ESTRO-ESP patient risk assessment categories using integrated molecular risk assessment.